2020
DOI: 10.3390/antibiotics9040162
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Gram-Negative Bacteria from Wild Captured Loggerhead Sea Turtles

Abstract: Sea turtles have been proposed as health indicators of marine habitats and carriers of antibiotic-resistant bacterial strains, for their longevity and migratory lifestyle. Up to now, a few studies evaluated the antibacterial resistant flora of Mediterranean loggerhead sea turtles (Caretta caretta) and most of them were carried out on stranded or recovered animals. In this study, the isolation and the antibiotic resistance profile of 90 Gram negative bacteria from cloacal swabs of 33 Mediterranean wild captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 49 publications
5
42
0
2
Order By: Relevance
“…S. aureus is one of the bacterial species with a higher ability to acquire antibiotic resistance determinants and is usually associated with a multidrug-resistant profile. Antibiotic-resistant bacteria and antibiotic resistance genes were also described in marine environments, such as the Mediterranean Sea and its seacoast [8], and in wild marine animals, such as healthy sea turtles [9]. These studies confirmed that Gram-negative bacteria are most frequently found in samples deriving from the marine environment.…”
mentioning
confidence: 61%
“…S. aureus is one of the bacterial species with a higher ability to acquire antibiotic resistance determinants and is usually associated with a multidrug-resistant profile. Antibiotic-resistant bacteria and antibiotic resistance genes were also described in marine environments, such as the Mediterranean Sea and its seacoast [8], and in wild marine animals, such as healthy sea turtles [9]. These studies confirmed that Gram-negative bacteria are most frequently found in samples deriving from the marine environment.…”
mentioning
confidence: 61%
“…Similarly, several new agents for the treatment of methicillin-resistant S. aureus (MRSA) are currently undergoing clinical trials, although these data in real-life terms are limited and require further investigations [ 21 ]. Moreover, the increase in antibiotic-resistant phenotypes and antibiotic resistance genes in different environments [ 22 ] and widely different organisms [ 23 ] requires urgent identification and development, at an industrial level, of new antimicrobial solutions. In this context, highly desirable new anti-pseudomonal and -staphylococcal antimicrobials should not drive superinfection [ 20 ] and be preferably available as oral formulations to allow step-down therapy in the treatment of both Gram-negative and -positive infections [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both A. hydrophila and C. freundii are documented pathogens found among both freshwater and marine chelonians, and include antibiotic-resistant forms [ 85 , 86 , 87 ]. The study of antibiotic-resistant bacteria in marine turtles may also be used as a bio-indicator of exposure to effluents and other sources of environmental contamination [ 88 , 89 ]. Thus, turtles are a “sentinel species” for ecosystem health [ 90 , 91 ].…”
Section: Introductionmentioning
confidence: 99%